The Effects of Using Paper and Electronic Monolingual English Learners’ Dictionaries while Reading on Students In-depth Vocabulary knowledge - BENZITOUNI, Amina Ouafa (Journal of Human Sciences, 2016)
Learning new words is a primary concern for most learners. Accordingly, many EFL students make use of English-English dictionaries, paper and electronic to develop their vocabulary. The purpose of this quasi-experimental study is to examine the effects of using dictionaries on students’ in-depth vocabulary knowledge. The results showed that students’ in-depth vocabulary knowledge improved when they used their dictionaries, in particular electronic ones. Thus, using dictionaries as a learning tool deserves more attention in the context of EFL vocabulary learning and teaching.